(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Further observations on the presence of this parasitoid in Basilicata and Apulia (southern Italy) were carried out from September 2007 to March 2008. Results show that C. chamaeleon is able to emerge even in full winter, whilst emergence of its host, Ophelimus maskelli (Ashmead), is either very poor or null at all. Samples of nearly 200 leaves of Eucalyptus camaldulensis Dehnh. were collected in 4 localities, where a conspicuous presence of this parasitoid had been detected in the summer 2007. Although differing in number, adults of C. chamaeleon were obtained from all samples.